Prevalence of adults who are the targets of parental alienating behaviors and their impact. (November 2019) - Harman, Jennifer J.; Leder-Elder, Sadie; Biringen, Zeynep
Abstract: Estimating the prevalence of parental alienation is challenging because not all children who are exposed to parental alienating behaviors become alienated (Harman, Bernet, & Harman, 2019). The purpose of the current study was to determine whether the proportion of adults who indicate being alienated from a child will be similar to results from a previous poll of North Carolina adults (Harman, Leder-Elder, & Biringen, 2016) using three nationally representative on-line survey panels from United States and Canada, and to determine the mental health impact of parental alienating behaviors. Results from the first two polls indicate that the prevalence of parents who feel they are being alienated from their children is higher than originally estimated: 35.5% (of 273) in the U.S. and 32% (of 397) in Canada. Using another means of assessment for the third poll, 39.1% (of 594) of parents in the US are the non-reciprocating targets of parental alienating behaviors, which is over 22 million parents and confirms previous estimates that did not differentiate between reciprocating and non-reciprocating parents (Harman et al., 2016). Of these, 6.7% of the parents had children who were moderately to severely alienated, which is at least 1.3% of the US population. Alienated parents also had high levels of depression, trauma symptoms, and risk for suicide. Ramifications of these findings for researchers and practitioners are discussed. Highlights: Over 30% of parents in the U.S. and Canada feel they are being alienated from a child by the other parent. About 22 million American parents are the targets of parental alienation behaviors and are not reciprocating these in kind. Over 3.8 million children in the U.S. are estimated to be moderately to severely alienated from a parent · Parents who reciprocated alienating behaviors (loyalty conflicts) were not likely to be alienated from a child. About half of parents who have been alienated from their child have considered committing suicide within the last year.